2021
DOI: 10.1177/20587384211027679
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and corresponding immune function status of recurrent viral polymerase chain reaction positivity in patients with COVID-19 : A meta- analysis and systematic review

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) was declared a global pandemic in March 2020. Since then, several studies have found COVID-19 patients with recurrent viral polymerase chain reaction (PCR) positivity. Methods: On May 6, 2021, an exhaustive literature search of the Web of Science, PubMed, Cochrane Library, Chinese National Knowledge Infrastructure databases, Embase, Wan Fang Data, VIP database, Sinomed database, BioRxiv, MedRxiv, and Research Square was conducted to find describing the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Moreover, the use of tocilizumab, a blocker of IL-6 receptor (IL-6R), has been recommended for severe cases of COVID-19 ( Huang et al., 2020 ; Ruan et al., 2020 ; Wu et al., 2020a ; Angriman et al., 2021 ; Galván-Román et al., 2021 ; Mcelvaney et al., 2021 ). IL-6 is also reported as one of the good predictors of progression and severity in patients with COVID-19 ( Guirao et al., 2020 ; Liu et al., 2020 ; Broman et al., 2021 ; Ren et al., 2021 ). In addition, it is suggested that an elevated level of IL-6 is an important predictor of patients with severe COVID-19 needing ventilator support ( Galván-Román et al., 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the use of tocilizumab, a blocker of IL-6 receptor (IL-6R), has been recommended for severe cases of COVID-19 ( Huang et al., 2020 ; Ruan et al., 2020 ; Wu et al., 2020a ; Angriman et al., 2021 ; Galván-Román et al., 2021 ; Mcelvaney et al., 2021 ). IL-6 is also reported as one of the good predictors of progression and severity in patients with COVID-19 ( Guirao et al., 2020 ; Liu et al., 2020 ; Broman et al., 2021 ; Ren et al., 2021 ). In addition, it is suggested that an elevated level of IL-6 is an important predictor of patients with severe COVID-19 needing ventilator support ( Galván-Román et al., 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, recent animal experiments have revealed a strong correlation between IL-6 and TNF-α and the pathological progression of Streptococcus pneumoniae-induced pneumonia [6]. The latest research suggests that the in ammatory response plays a pivotal role in coronavirus disease 2019 (COVID- 19), while an excessive release of in ammatory cytokines exacerbates the severity of COVID-19 [7]. The serum levels of IL-6 and CRP exhibit a signi cant correlation with the severity of COVID-19, thereby serving as independent prognostic factors for disease risk prediction [8].…”
Section: Introductionmentioning
confidence: 99%